Faktor Yang Berhubungan Dengan Kepatuhan Dalam Penggunaan APD Pada Pekerja Workshop Di PT. Pelindo - Manis, Siti Nur; A. Fachrin, Suharni; Hidayat (Window of Public Health Journal, 2025)
According to 2018 International Labour Organization (ILO) data, globally, there are 60,000 fatal accidents per year. Approximately 1 in 6 reported fatal accidents occur in the construction sector. The number of workplace accidents in Indonesia is relatively high. This is due to the still weak awareness of workers. This study aimed to determine factors related to compliance in the use of Personal Protective Equipment (PPE) among workshop workers at PT Pelindo Terminal Petikemas New Makassar Terminal 2. This type of research uses quantitative methods with a cross-sectional study design. The sampling technique used was total sampling with a total of 40 respondents. Data were obtained using a questionnaire. Data were analyzed using the chi-square test at a 95% confidence level (alpha = 0.05) and from the results of the study obtained that the variables related to compliance in the use of PPE are attitudes (p-value = 0.040) and availability of PPE (p-value = 0.039) while those that are not related are Education (p-value = 0.392), knowledge (p-value = 1.000) and supervision (p-value = 0.369). It can be concluded that there is no relationship between Education, compliance, and supervision, and there is a relationship between attitudes and availability of PPE with compliance in the use of personal protective equipment. The study's findings suggest that PT Pelindo Terminal Petikemas New Makassar Terminal 2 should implement a stricter K3 system and routinely provide guidance in the proper use of PPE, which could significantly improve workplace safety.